Analysis of the structure of linseed flax varieties based on polymorphic microsatellite loci - S. Z. Guchetl; T. A. Chelyustnikova; A. A. Averina (Аграрная наука Евро-Северо-Востока, 2022)
High profitability of linseed flax production is an incentive for developing new varieties with high yield performance and for expansion of cultivation areas. The restricted genetic diversity of Linum usitatissimum L. due to selfpollination and of initial forms used by developing the new linseed flax varieties limits the efficiency of the breeding work. The purpose of the research was to determine the genetic structure of linseed flax varieties using a system of 10 microsatellite loci. Four varieties bred by the V. S. Pustovoit All-Russian Research Institute of Oil Crops were used as the research material. DNA was isolated by the CTAB method. Electrophoretic separation of amplicons was performed in 8 % polyacrylamide gel followed by ethidium bromide staining. The determination of the main indicators of genetic variability, analyzed molecular variance (AMOVA), the Wright F-statistics indicators, and the principal coordinates analysis (PCoA) was carried out using the GenAlEx 6.5 program. A total of 53 alleles have been identified. The main indicators of genetic diversity were calculated for each variety. According to statistical characteristics (Na, Ne, I, F), the variety Nilin is the source of the greatest genetic diversity. For all varieties, the ratio of expected heterozygosity (He) and observed heterozygosity (Ho) corresponds to inbred populations with a minimum proportion of random crossing. By the allelic state of the 10 SSR loci, the variety Snegurok belongs to the linear type, which corresponds to its origin. The genetic passport of this variety has been compiled according to these loci. According to the results of the analysis of molecular variance (AMOVA), 71 % of the total dispersion is due to genetic differences between the varieties, and 29 % is due to intra-varietal differences.